Las ciencias sociales y la vida real - Oscar F. Contreras (Estudios sobre las Culturas Contemporáneas)
Description of the manner in which the work of the social scientist, especially the sociologist, is pereeived. It rescues the problematic of social science today and defends it from the discredit that this discipline has suffered, revalorizing the functions and commitments of all of those involved in the social sciences in contemporaiy Mexico.